PENGARUH PEMBERIAN STIMULUS MUSICAL FRISSON TERHADAP PERFORMA MEMORI JANGKA PENDEK - Christopher Alvaro Dharmawan,* Yosef Purwoko,** Maria Belladonna Rahmawati,*** Hexanto Muhartomo*** (NEURONA, 2020)
INTRODUCTION A PERSONS INTELLIGENCE MAY BE DETERMINED BY THE CAPACITY OF WORKING AND SHORTTERM MEMORY STIMULATIONS RESTRAIN THE EARLYONSET NEURODEGENERATIVE PROCESS AND SHORTTERM MEMORY LOSS MUSICAL FRISSON STIMULATION CAN INCREASE THE PRODUCTION OF DOPAMINE BLOOD FLOW AND ACTIVITIES OF SOME PARTS OF THE BRAIN THAT HAVE ROLES IN SHORTTERM MEMORY PROCESS